Billy Summers : A Novel - King, Stephen 1947-; Sparks, Paul 1971- (New York, NY : AudioWorks, 2021)
"Billy Summers is a man in a room with a gun. He's a killer for hire and the best in the business. But he'll do the job only if the target is a truly bad guy. And now Billy wants out. But first there is one last hit. Billy is among the best snipers in the world, a decorated Iraq war vet, a Houdini when it comes to vanishing after the job is done. So what could possibly go wrong?"
Keywords: Assassins -- Fiction; Murder for hire -- Fiction; Undercover operations -- Fiction; Good and evil -- Fiction; Justice -- Fiction; Revenge -- Fiction; Rape victims -- Fiction; Secrecy -- Fiction; Snipers -- Fiction; Iraq War, 2003-2011 -- Fiction -- Veterans; Novelists -- Fiction; Noir fiction; Thrillers (Fiction); Audiobooks